Advancing ocean sustainability through better science integration: perspectives of Early Career Ocean Professionals - Vozzo, Maria L.; Christofidis, Marina; Griffiths, Laura; Kelly, Rachel; Manion, Michelle L.; Barmand, Shayan; Bolin, Jessica A.; Fuenzalida-Miralles, Pablo A.; Harris, Melanie L.; Issell, Abby; Kuempel, Caitlin D.; Martinez Diaz, Marycarmen; et al. (Frontiers in Ocean Sustainability, 2025)
As the United Nations Decade of Ocean Science for Sustainable Development (2021–2030) approaches halfway, inclusive input on progress and innovative approaches to achieving ocean sustainability is timely and necessary. Input from the leaders of tomorrow—today's Early Career Ocean Professionals (ECOPs)—brings important generational perspectives on delivering marine science that can inform and contribute to achieving future ocean sustainability. ECOP perspectives may also offer novel insights on informing solutions to ocean-related challenges. Here, we articulate ECOP perspectives on priority recommendations for addressing current gaps and opportunities in ocean science in the context of the “Ocean Decade”. These recommendations include: (1) a culture shift toward more active and transparent data sharing; (2) valuing and connecting different knowledge systems; and (3) achieving effective knowledge-sharing across disciplines and jurisdictions. We outline how all actors in ocean research, across different disciplines and institutions, can implement these changes, and where relevant, demonstrate unique roles ECOPs can play in this process. We propose that the implementation of these recommendations, by all actors in ocean science, along with greater inclusion and transfer of diverse knowledge, will support efforts to achieve the goals of the Ocean Decade, and ensure ocean sustainability for generations to come.